Τὸν ἄρτον ἡμῶν τὸν ἐπιούσιον δὸς ἡμῖν σήμερον (Mt 6:11; Lk 11:3): The Lord"s Prayer and an African predicament – the Ewe-Ghanaian context in focus - Sakitey, Daniel (HTS teologiese studies, 2020)
This article seeks to reconstruct the phrase τὸν ἄρτον ἡμῶν τὸν ἐπιούσιον (Mt 6:11; Lk 11:3) in the light of an African predicament with the Ewe-Ghanaian context in focus. The article posits that the various interpretations of the phrase throughout the epochs of Christianity have arisen as a result of the ambiguity associated with ἐπιούσιος and the quest to make the Lord’s Prayer in general relevant to the life situation of the recipient communities. Although the Lord’s Prayer is still regarded as a prayer par excellence in the Ewe-Ghanaian Christian community, its central theme in popular Ewe-Ghanaian spirituality has been demonological instead of eschatological. The demonological interpretation is premised on the primal Ewe belief that successful spiritual warfare against the evil forces believed to be militating against one’s destiny in life can restore one’s fortunes and lead to the blessing of material prosperity. Thus, the phrase τὸν ἄρτον ἡμῶν τὸν ἐπιούσιον (Mt 6:11; Lk 11:3) in popular Ewe-Ghanaian Christian spirituality is a call on God to ‘grant us the blessing of material prosperity, good health and longevity’. The demonological approach towards material prosperity, however, is discontinuous with the evangelisation approach, which was introduced into Ewe-Ghanaian spirituality through missionary activities in the mid-19th century. The missionaries identified the cardinal Ewe-Ghanaian predicament – poverty of the mind and spirit – and addressed them holistically through the message of the Gospel and the establishment of schools, hospitals, and agriculture to guarantee food security. This holistic approach to alleviating the poverty of the spirit and mind laid the foundation for the socio-economic development of their Ewe-Ghanaian Christian converts and the communities in which they practise their faith.Contribution: This article forms part of the researcher’s contribution to the academic knowledge on the Lord’s Prayer and inspires the use of Mother Tongue Biblical hermeneutics in the development of theological materials for the Ewe-Ghanaian Christian communities in Ghana, Togo, and Benin.